Acceptance of E-Hailing System for Grocery Delivery Services in Urban Area - Mat Yajid, Muhammad Ilham; Ambak, Kamarudin (Recent Trends in Civil Engineering and Built Environment, 2023)
E-Hailing services provide sharing economy between customers and service provider. This system applying the use of technologies in the service that will give benefit to many parties especially on grocery delivery services. This study aims to determine the level of acceptance of customers towards e-Hailing system on grocery deliveries in urban areas. The objectives are to determine the contributing factor to the acceptance of grocery delivery services in urban areas and to evaluate the level of user acceptance between registered and unregistered company in providing such services. The questionnaire was distributed to the communities or residents in Klang Valley. The location of the study was focused on the Klang Valley where there are major cities that is suitable for this study. The online survey platform (Google Form) was used to design questions and was distributed to respondents for this study. The survey was distributed to 203 respondents. Survey questions are designed based on the Technology Acceptance Model (TAM). Descriptive, correlation and regression analysis were performed to analyze data obtained from the questionnaire. The findings showed that the factors that most contributed to the adoption of the e-Hailing system of grocery delivery services in urban areas is Perceived Ease of Use (PeOU), whereby the confidence of existing services is more efficient and safer. The companies that registered with The Company of Malaysia (SSM) are the preferred choice for consumers in the Klang Valley over companies not registered with SSM. There is a significant relationship between behavioral intent (BI) and the actual use of the system (ASU). Among the proposed improvements to grocery delivery services is to increase the number of rider of goods in a district to assist in the speed of delivery of goods and the delivery time of groceries to the consumers.